Pengaruh Postpurchase Price Perception dan Postpurchase Performance Perceptions Terhadap Satisfaction - Yudhiantoro, Danang (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2009)
University Ã‚Â needs Ã‚Â the Ã‚Â trust Ã‚Â from Ã‚Â people Ã‚Â with Ã‚Â quality Ã‚Â assurance, Ã‚Â quality control, Ã‚Â and Ã‚Â qualityÃ‚Â improvement. Ã‚Â The Ã‚Â quality Ã‚Â assurance Ã‚Â and Ã‚Â quality improvement Ã‚Â can Ã‚Â be Ã‚Â doing Ã‚Â with Ã‚Â nationalÃ‚Â accreditation. Ã‚Â They Ã‚Â need Ã‚Â evaluation about Ã‚Â customer Ã‚Â satisfaction, Ã‚Â from Ã‚Â their Ã‚Â perception Ã‚Â aboutÃ‚Â price, etc.Using linear regression with SPSS serial 16 to measure and explain the result from thisÃ‚Â concept, Ã‚Â the Ã‚Â overall Ã‚Â impact Ã‚Â of Ã‚Â Postpurchase Ã‚Â Price Ã‚Â Perception Ã‚Â and Postpurchase Ã‚Â PerformanceÃ‚Â Perception on satisfaction is positive. The implications of these findings for research, practice,Ã‚Â and theory are discussed.